A deep spectromorphological study of the γ -ray emission surrounding the young massive stellar cluster Westerlund 1 - Aharonian, F.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Becherini, Y.; Berge, D.; Bi, B.; Böttcher, Markus; De Lavergne, M. De Bony; Bradascio, F.; Brose, R.; Brun, F.; et al. (Astronomy & Astrophysics, 2022)
Context. Young massive stellar clusters are extreme environments and potentially provide the means for efficient particle acceleration. Indeed, they are increasingly considered as being responsible for a significant fraction of cosmic rays (CRs) that are accelerated within the Milky Way. Westerlund 1, the most massive known young stellar cluster in our Galaxy, is a prime candidate for studying this hypothesis. While the very-high-energy γ-ray source HESS J1646-458 has been detected in the vicinity of Westerlund 1 in the past, its association could not be firmly identified. Aims. We aim to identify the physical processes responsible for the γ-ray emission around Westerlund 1 and thus to understand the role of massive stellar clusters in the acceleration of Galactic CRs better. Methods. Using 164 h of data recorded with the High Energy Stereoscopic System (H.E.S.S.), we carried out a deep spectromorphological study of the γ-ray emission of HESS J1646-458. We furthermore employed H I and CO observations of the region to infer the presence of gas that could serve as target material for interactions of accelerated CRs. Results. We detected large-scale ( 2 diameter) γ-ray emission with a complex morphology, exhibiting a shell-like structure and showing no significant variation with γ-ray energy. The combined energy spectrum of the emission extends to several tens of TeV, and it is uniform across the entire source region. We did not find a clear correlation of the γ-ray emission with gas clouds as identified through H I and CO observations. Conclusions. We conclude that, of the known objects within the region, only Westerlund 1 can explain the majority of the γ-ray emission. Several CR acceleration sites and mechanisms are conceivable and discussed in detail. While it seems clear that Westerlund 1 acts as a powerful particle accelerator, no firm conclusions on the contribution of massive stellar clusters to the flux of Galactic CRs in general can be drawn at this point.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Acceleration of particles; Galaxies: star clusters: individual: Westerlund 1; Gamma rays: general; Radiation mechanisms: non-thermal; Shock waves; Stars: massive

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schüssler, F.; Stappers, B. W.; Venter, C.; Heywood; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

Analysis of the HESS public data release with ctools - Knodlseder, J.; Tibaldo, L.; Tiziani, Domenico; Specovius, Andreas; Cardenzana, J.; Mayer, M.; Kelley-Hoskins, N.; Di Venere, L.; Bonnefoy, S.; Ziegler, A.; Eschbach, Stefan; Martin, P.; et al. (Astronomy & Astrophysics, 2019)
The ctools open-source software package was developed for the scientific analysis of astronomical data from Imaging Air Cherenkov Telescopes (IACTs), such as H.E.S.S., VERITAS, MAGIC, and the future Cherenkov Telescope Array (CTA). To date, the software has been mainly tested using simulated CTA data; however, upon the public release of a small set of H.E.S.S. observations of the Crab nebula, MSH 15-52, RX J1713.7-3946, and PKS 2155-304 validation using real data is now possible. We analysed the data of the H.E.S.S. public data release using ctools version 1.6 and compared our results to those published by the H.E.S.S. Collaboration for the respective sources. We developed a parametric background model that satisfactorily describes the expected background rate as a function of reconstructed energy and direction for each observation. We used that model, and tested all analysis methods that are supported by ctools, including novel unbinned and joint or stacked binned analyses of the measured event energies and reconstructed directions, and classical On-Off analysis methods that are comparable to those used by the H.E.S.S. Collaboration. For all analysis methods, we found a good agreement between the ctools results and the H.E.S.S. Collaboration publications considering that they are not always directly comparable due to differences in the datatsets and event processing software. We also performed a joint analysis of H.E.S.S. and Fermi-LAT data of the Crab nebula, illustrating the multi-wavelength capacity of ctools. The joint Crab nebula spectrum is compatible with published literature values within the systematic uncertainties. We conclude that the ctools software is mature for the analysis of data from existing IACTs, as well as from the upcoming CTA.
CRIS-Team WoS Importer:2020-01-03

A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, H.; Adam, R.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Barnard, M.; et al. (Nature, 2019)
Gamma-ray bursts (GRBs) are brief flashes of γ-rays and are considered to be the most energetic explosive phenomena in the Universe1. The emission from GRBs comprises a short (typically tens of seconds) and bright prompt emission, followed by a much longer afterglow phase. During the afterglow phase, the shocked outflow—produced by the interaction between the ejected matter and the circumburst medium—slows down, and a gradual decrease in brightness is observed2. GRBs typically emit most of their energy via γ-rays with energies in the kiloelectronvolt-to-megaelectronvolt range, but a few photons with energies of tens of gigaelectronvolts have been detected by space-based instruments3. However, the origins of such high-energy (above one gigaelectronvolt) photons and the presence of very-high-energy (more than 100 gigaelectronvolts) emission have remained elusive4. Here we report observations of very-high-energy emission in the bright GRB 180720B deep in the GRB afterglow—ten hours after the end of the prompt emission phase, when the X-ray flux had already decayed by four orders of magnitude. Two possible explanations exist for the observed radiation: inverse Compton emission and synchrotron emission of ultrarelativistic electrons. Our observations show that the energy fluxes in the X-ray and γ-ray range and their photon indices remain comparable to each other throughout the afterglow. This discovery places distinct constraints on the GRB environment for both emission mechanisms, with the inverse Compton explanation alleviating the particle energy requirements for the emission observed at late times. The late timing of this detection has consequences for the future observations of GRBs at the highest energies.
CRIS-Team Scopus Importer:2019-12-03

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

Detection of very-high-energy γ -ray emission from the colliding wind binary η Car with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Aims. Colliding wind binary systems have long been suspected to be high-energy (HE; 100 MeV < E < 100 GeV) γ-ray emitters. η Car is the most prominent member of this object class and is confirmed to emit phase-locked HE γ rays from hundreds of MeV to 100 GeV energies. This work aims to search for and characterise the very-high-energy (VHE; E >100 GeV) γ-ray emission from η Car around the last periastron passage in 2014 with the ground-based High Energy Stereoscopic System (H.E.S.S.). Methods. The region around η Car was observed with H.E.S.S. between orbital phase p = 0.78-1.10, with a closer sampling at p ≈ 0.95 and p ≈ 1.10 (assuming a period of 2023 days). Optimised hardware settings as well as adjustments to the data reduction, reconstruction, and signal selection were needed to suppress and take into account the strong, extended, and inhomogeneous night sky background (NSB) in the η Car field of view. Tailored run-wise Monte-Carlo simulations (RWS) were required to accurately treat the additional noise from NSB photons in the instrument response functions. Results. H.E.S.S. detected VHE γ-ray emission from the direction of η Car shortly before and after the minimum in the X-ray light-curve close to periastron. Using the point spread function provided by RWS, the reconstructed signal is point-like and the spectrum is best described by a power law. The overall flux and spectral index in VHE γ rays agree within statistical and systematic errors before and after periastron. The γ-ray spectrum extends up to at least 400 GeV. This implies a maximum magnetic field in a leptonic scenario in the emission region of 0.5 Gauss. No indication for phase-locked flux variations is detected in the H.E.S.S. data.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Astroparticle physics; Binaries: general; Cosmic rays; Radiation mechanisms: non-thermal; Stars: individual: η Car; Stars: Wolf-Rayet

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Evidence of 100 TeV gamma-ray emission from HESS J1702-420: A new PeVatron candidate - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan; Martins, V. Barbosa; Barnacka, A.; et al. (Astronomy & Astrophysics, 2021)
Aims. The identification of PeVatrons, hadronic particle accelerators reaching the knee of the cosmic ray spectrum (few x 10(15) eV), is crucial to understand the origin of cosmic rays in the Galaxy. We provide an update on the unidentified source HESS J1702-420, a promising PeVatron candidate.
CRIS-Team WoS Importer:2021-10-15
Keywords: Cosmic rays; Gamma rays: general; Methods: data analysis; Radiation mechanisms: non-thermal

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

Gamma-ray emission from molecular clouds illuminated by local young massive stellar clusters and detection prospects with current and next generation instruments - Celli, S.; Specovius, Andreas; Mitchell, Alison; Morlino, G.; Menchiari, S. (Proceedings of Science, 2024)
Cosmic ray acceleration up to PeV energies has been suggested to take place in massive and young stellar clusters. The formation of a strong termination shock sustained by the collective action of stellar winds in a compact cluster offers a promising location where efficient particle acceleration might take place. The subsequent hadronic interactions of these particles result into gamma-ray production: in particular, if dense clouds are located within and around clusters, enhanced emission is expected. Within a scenario of particle acceleration at the cluster wind termination shock, we compute the emerging gamma-ray signal from molecular clouds illuminated by stellar clusters within the Milky Way. For this purpose, we adopt the Miville-Deschenes cloud catalog based on the Dame CO survey and astrometric observations of stellar clusters by GAIA. We further evaluate detection prospects of the gamma-ray flux with the Cherenkov Telescope Array (CTA) and the Large High Altitude Air Shower Observatory (LHAASO).
CRIS-Team Scopus Importer:2025-02-04

Gamma-ray observations of MAXI J1820+070 during the 2018 outburst - Abe, H.; Abe, S.; Acciari, V. A.; Aniello, T.; Ansoldi, S.; Antonelli, L. A.; Engels, A. Arbet; Arcaro, C.; Artero, M.; Asano, K.; Baack, D.; Babic, A.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
MAXIJ1820+070 is a low-mass X-ray binary with a black hole (BH) as a compact object. This binary underwent an exceptionally bright X-ray outburst from 2018 March to October, showing evidence of a non-thermal particle population through its radio emission during this whole period. The combined results of 59.5 h of observations of the MAXI J1820+070 outburst with the H.E.S.S., MAGIC and VERITAS experiments at energies above 200 GeV are presented, together with Fermi-LAT data between 0.1 and 500 GeV, and multiwavelength observations from radio to X-rays. Gamma-ray emission is not detected from MAXI J1820+070, but the obtained upper limits and the multiwavelength data allow us to put meaningful constraints on the source properties under reasonable assumptions regarding the non-thermal particle population and the jet synchrotron spectrum. In particular, it is possible to show that, if a high-energy (HE) gamma-ray emitting region is present during the hard state of the source, its predicted flux should be at most a factor of 20 below the obtained Fermi-LAT upper limits, and closer to them for magnetic fields significantly below equipartition. During the state transitions, under the plausible assumption that electrons are accelerated up to similar to 500 GeV, the multiwavelength data and the gamma-ray upper limits lead consistently to the conclusion that a potential HE and very-HE gamma-ray emitting region should be located at a distance from the BH ranging between 10(11) and 10(13) cm. Similar outbursts from low-mass X-ray binaries might be detectable in the near future with upcoming instruments such as CTA.
CRIS-Team WoS Importer:2023-01-27

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

LMC N132D: A mature supernova remnant with a power-law gamma-ray spectrum extending beyond 8 TeV - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2021)
Context. Supernova remnants (SNRs) are commonly thought to be the dominant sources of Galactic cosmic rays up to the knee of the cosmic-ray spectrum at a few PeV. Imaging Atmospheric Cherenkov Telescopes have revealed young SNRs as very-high-energy (VHE, >100 GeV) gamma-ray sources, but for only a few SNRs the hadronic cosmic-ray origin of their gamma-ray emission is indisputably established. In all these cases, the gamma-ray spectra exhibit a spectral cutoff at energies much below 100 TeV and thus do not reach the PeVatron regime. Aims. The aim of this work was to achieve a firm detection for the oxygen-rich SNR LMC N132D in the VHE gamma-ray domain with an extended set of data, and to clarify the spectral characteristics and the localization of the gamma-ray emission from this exceptionally powerful gamma-ray-emitting SNR. Methods. We analyzed 252 h of High Energy Stereoscopic System (H.E.S.S.) observations towards SNR N132D that were accumulated between December 2004 and March 2016 during a deep survey of the Large Magellanic Cloud, adding 104 h of observations to the previously published data set to ensure a > 5σ detection. To broaden the gamma-ray spectral coverage required for modeling the spectral energy distribution, an analysis of Fermi-LAT Pass 8 data was also included. Results. We unambiguously detect N132D at VHE with a significance of 5.7σ. We report the results of a detailed analysis of its spectrum and localization based on the extended H.E.S.S. data set. The joint analysis of the extended H.E.S.S and Fermi-LAT data results in a spectral energy distribution in the energy range from 1.7 GeV to 14.8 TeV, which suggests a high luminosity of N132D at GeV and TeV energies. We set a lower limit on a gamma-ray cutoff energy of 8 TeV with a confidence level of 95%. The new gamma-ray spectrum as well as multiwavelength observations of N132D when compared to physical models suggests a hadronic origin of the VHE gamma-ray emission. Conclusions. SNR N132D is a VHE gamma-ray source that shows a spectrum extending to the VHE domain without a spectral cutoff at a few TeV, unlike the younger oxygen-rich SNR Cassiopeia A. The gamma-ray emission is best explained by a dominant hadronic component formed by diffusive shock acceleration. The gamma-ray properties of N132D may be affected by an interaction with a nearby molecular cloud that partially lies inside the 95% confidence region of the source position.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cosmic rays; Gamma rays: General; ISM: Supernova remnants

Mass and wind luminosity of young Galactic open clusters in Gaia DR2 - Celli, S.; Specovius, Andreas; Menchiari, S.; Mitchell, Alison; Morlino, G. (Astronomy & Astrophysics, 2024)
Context. Star clusters constitute a significant part of the stellar population in our Galaxy. The feedback processes they exert on the interstellar medium impact multiple physical processes from the chemical to the dynamical evolution of the Galaxy. In addition, young and massive stellar clusters might act as efficient particle accelerators and contribute to the production of cosmic rays. Aims. We aim at evaluating the wind luminosity driven by the young (< 30 Myr) Galactic open stellar clusters observed by the Gaia space mission. This is crucial for determining the energy channeled into accelerated particles. Methods. To do this, we developed a method relying on the number, magnitude, and line-of-sight extinction of the stars observed per cluster. Assuming that the stellar mass function follows a Kroupa mass distribution and accounting for the maximum stellar mass allowed by the age and mass of the parent cluster, we conservatively estimated the mass and wind luminosity of 387 local clusters within the second data release of Gaia. Results. We compared the results of our computation with recent estimates of young cluster masses. With respect to these, our sample is three times more abundant, particularly above a few thousand solar masses. This is of the utmost relevance for predicting the gamma-ray emission resulting from the interaction of accelerated particles. The cluster wind luminosity distribution we obtained extends up to 3 × 1038 erg s-1. This is a promising feature in terms of potential particle acceleration scenarios.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Mass function; Open clusters and associations: general; Outflows; Stars: luminosity function; Stars: mass-loss; Stars: winds

Monte Carlo studies for the optimisation of the Cherenkov Telescope Array layout - Acharyya, A.; Agudo, I.; Angüner, E. O.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; Amans, J. P.; Amati, L.; Amato, E.; Ambrosi, G.; et al. (Astroparticle Physics, 2019)
The Cherenkov Telescope Array (CTA) is the major next-generation observatory for ground-based very-high-energy gamma-ray astronomy. It will improve the sensitivity of current ground-based instruments by a factor of five to twenty, depending on the energy, greatly improving both their angular and energy resolutions over four decades in energy (from 20 GeV to 300 TeV). This achievement will be possible by using tens of imaging Cherenkov telescopes of three successive sizes. They will be arranged into two arrays, one per hemisphere, located on the La Palma island (Spain) and in Paranal (Chile). We present here the optimised and final telescope arrays for both CTA sites, as well as their foreseen performance, resulting from the analysis of three different large-scale Monte Carlo productions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cherenkov telescopes; Cosmic rays; Gamma rays; IACT technique; Monte Carlo simulations

Observation of the Gamma-Ray Binary HESS J0632+057 with the HESS, MAGIC, and VERITAS Telescopes - Adams, C. B.; Benbow, W.; Brill, A.; Buckley, J. H.; Capasso, M.; Chromey, A. J.; Errando, M.; Falcone, A.; Farrell, K. A.; Feng, Q.; Finley, J. P.; Foote, G. M.; et al. (Astrophysical Journal, 2021)
The results of gamma-ray observations of the binary system HESS J0632 + 057 collected during 450 hr over 15 yr, between 2004 and 2019, are presented. Data taken with the atmospheric Cherenkov telescopes H.E.S.S., MAGIC, and VERITAS at energies above 350 GeV were used together with observations at X-ray energies obtained with Swift-XRT, Chandra, XMM-Newton, NuSTAR, and Suzaku. Some of these observations were accompanied by measurements of the H alpha emission line. A significant detection of the modulation of the very high-energy gamma-ray fluxes with a period of 316.7 +/- 4.4 days is reported, consistent with the period of 317.3 +/- 0.7 days obtained with a refined analysis of X-ray data. The analysis of data from four orbital cycles with dense observational coverage reveals short-timescale variability, with flux-decay timescales of less than 20 days at very high energies. Flux variations observed over a timescale of several years indicate orbit-to-orbit variability. The analysis confirms the previously reported correlation of X-ray and gamma-ray emission from the system at very high significance, but cannot find any correlation of optical H alpha parameters with fluxes at X-ray or gamma-ray energies in simultaneous observations. The key finding is that the emission of HESS J0632 + 057 in the X-ray and gamma-ray energy bands is highly variable on different timescales. The ratio of gamma-ray to X-ray flux shows the equality or even dominance of the gamma-ray energy range. This wealth of new data is interpreted taking into account the insufficient knowledge of the ephemeris of the system, and discussed in the context of results reported on other gamma-ray binary systems.
CRIS-Team WoS Importer:2022-01-14

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Probing the Magnetic Field in the GW170817 Outflow Using HESS Observations - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal Letters, 2020)
The detection of the first electromagnetic counterpart to the binary neutron star (BNS) merger remnant GW170817 established the connection between short gamma-ray bursts and BNS mergers. It also confirmed the forging of heavy elements in the ejecta (a so-called kilonova) via the r-process nucleosynthesis. The appearance of nonthermal radio and X-ray emission, as well as the brightening, which lasted more than 100 days, were somewhat unexpected. Current theoretical models attempt to explain this temporal behavior as either originating from a relativistic off-axis jet or a kilonova-like outflow. In either scenario, there is some ambiguity regarding how much energy is transported in the nonthermal electrons versus the magnetic field of the emission region. Combining the Very Large Array (radio) and Chandra (X-ray) measurements with observations in the GeV-TeV domain can help break this ambiguity, almost independently of the assumed origin of the emission. Here we report for the first time on deep H.E.S.S. observations of GW170817/GRB 170817A between 124 and 272 days after the BNS merger with the full H.E.S.S. array of telescopes, as well as on an updated analysis of the prompt (<5 days) observations with the upgraded H.E.S.S. phase-I telescopes. We discuss implications of the H.E.S.S. measurement for the magnetic field in the context of different source scenarios.
CRIS-Team WoS Importer:2020-05-29

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for dark matter signals towards a selection of recently detected DES dwarf galaxy satellites of the Milky Way with HESS - Abdallah, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2020)
Dwarf spheroidal galaxy satellites of the Milky Way are prime targets for indirect detection of dark matter with gamma rays due to their proximity, high dark matter content, and absence of nonthermal emission processes. Recently, the Dark Energy Survey (DES) revealed the existence of new ultrafaint dwarf spheroidal galaxies in the southern-hemisphere sky, therefore ideally located for ground-based observations with the imaging atmospheric Cherenkov telescope array H.E.S.S. We present a search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emission using H.E.S.S. observations carried out recently towards Reticulum II, Tucana II, Tucana III, Tucana IV, and Grus II satellites. No significant very-high-energy gamma-ray excess is found from the observations on any individual object nor in the combined analysis of all the datasets. Using the most recent modeling of the dark matter distribution in the dwarf galaxy halo, we compute for the first time on DES satellites individual and combined constraints from Cherenkov telescope observations on the annihilation cross section of dark matter particles in the form of Weakly Interacting Massive Particles. The combined 95% C.L. observed upper limits reach similar or equal to 1 x 10(-23) cm(3) s(-1) in the W+W- channel and 4 x 10(-26) cm(3) s(-1) in the gamma gamma channels for a dark matter mass of 1.5 TeV. The H.E.S.S. constraints well complement the results from Fermi-LAT, HAWC, MAGIC, and VERITAS and are currently the most stringent in the gamma gamma channels in the multi-GeV/multi-TeV mass range.
CRIS-Team WoS Importer:2020-09-18

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

Simultaneous observations of the blazar PKS 2155-304 from ultra-violet to TeV energies - Abdalla, H.; Adam, R.; Mitchell, Alison; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Here we report the results of the first ever contemporaneous multi-wavelength observation campaign on the BL Lac object PKS 2155-304 involving Swift, NuSTAR, Fermi-LAT, and H.E.S.S. The use of these instruments allows us to cover a broad energy range, which is important for disentangling the different radiative mechanisms. The source, observed from June 2013 to October 2013, was found in a low flux state with respect to previous observations but exhibited highly significant flux variability in the X-rays. The high-energy end of the synchrotron spectrum can be traced up to 40 keV without significant contamination by high-energy emission. A one-zone synchrotron self-Compton model was used to reproduce the broadband flux of the source for all the observations presented here but failed for previous observations made in April 2013. A lepto-hadronic solution was then explored to explain these earlier observational results.
CRIS-Team WoS Importer:2020-08-07

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Towards a 3D likelihood analysis in very-high-energy γ-ray astronomy: The case of H.E.S.S. - Mohrmann, Lars; Nakashima, Kaori; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; van Eldik, Christopher; Ohm, Stefan (Proceedings of Science, 2019)
The estimation of the residual background due to cosmic ray-induced air showers represents a key element of every analysis of Imaging Atmospheric Cherenkov Telescope (IACT) data. In the past, most techniques have relied on a measurement of the background in supposedly source-free regions within the observed field of view. However, this approach is problematic in regions with many (potentially overlapping) γ-ray sources or large-scale diffuse γ-ray emission, like e.g. the Galactic Plane. For these cases, a template-based 3D likelihood analysis might be superior. In this approach, a spectro-morphological model template, consisting of one or multiple source components and a background component, is fit to the data, resulting in a complete spectral and spatial description of the field of view. In this contribution, we present our efforts to establish a 3D likelihood analysis for data taken with the H.E.S.S. system of IACTs, using the open-source analysis packages ctools and Gammapy. In particular, we focus on the development of a template model for the cosmic ray-induced background - a major challenge in such an approach - from archival H.E.S.S. data. We characterise the obtained model and demonstrate its application using publicly available H.E.S.S. data. The validation of this analysis approach on experimental data also constitutes an important step towards the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team Scopus Importer:2021-04-20

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

Validation of open-source science tools and background model construction in gamma-ray astronomy - Mohrmann, Lars; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; Malyshev, Dmitry; Nakashima, Kaori; van Eldik, Christopher (Astronomy & Astrophysics, 2019)
In classical analyses of gamma-ray data from imaging atmospheric Cherenkov telescopes (IACTs), such as the High Energy Stereoscopic System (H.E.S.S.), aperture photometry, or photon counting, is applied in a (typically circular) region of interest (RoI) encompassing the source. A key element in the analysis is to estimate the amount of background in the RoI due to residual cosmic ray-induced air showers in the data. Various standard background estimation techniques have been developed in the last decades, most of them rely on a measurement of the background from source-free regions within the observed field of view. However, in particular in the Galactic plane, source analysis and background estimation are hampered by the large number of, sometimes overlapping, gamma-ray sources and large-scale di ffuse gamma-ray emission. For complicated fields of view, a three-dimensional (3D) likelihood analysis shows the potential to be superior to classical analysis. In this analysis technique, a spectromorphological model, consisting of one or multiple source components and a background component, is fitted to the data, resulting in a complete spectral and spatial description of the field of view. For the application to IACT data, the major challenge of such an approach is the construction of a robust background model. In this work, we apply the 3D likelihood analysis to various test data recently made public by the H.E.S.S. collaboration, using the open analysis frameworks ctools and Gammapy. First, we show that, when using these tools in a classical analysis approach and comparing to the proprietary H.E.S.S. analysis framework, virtually identical high-level analysis results, such as field-of-view maps and spectra, are obtained. We then describe the construction of a generic background model from data of H.E.S.S. observations, and demonstrate that a 3D likelihood analysis using this background model yields high-level analysis results that are highly compatible with those obtained from the classical analyses. This validation of the 3D likelihood analysis approach on experimental data is an important step towards using this method for IACT data analysis, and in particular for the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team WoS Importer:2020-01-17

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal